MODELLING OF SIDE ELECTROMAGNETIC RADIATIONS OF PC BY THE METHOD OF MOMENTS - A. G. Filippovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Achieved the electrodynamic model of PC as source of side electromagnetic radiations based on the method of moments. The results of experiments confirming efficiency of model are given.